Interaction between oscillating-grid turbulence and a solid impermeable boundary - McCorquodale, Mark W. (2018)
The interaction of a boundary with turbulence is a defining feature of many turbulent flows, resulting in a turbulent boundary layer which plays a prominent role in the production and dissipation of turbulence. Commonly, this interaction is dominated by the effects of mean shear. However, more subtle aspects of the interaction, such as effects associated with turbulent motions impinging onto the boundary, are still thought to play a key role in giving rise to the boundary layer structure. Unfortunately, these aspects of the interaction are currently poorly understood. A better understanding of these aspects of the interaction may be derived by isolating them from the effects of mean shear through the study of zero-mean-shear turbulence interacting with a boundary.